Brand Image PENGARUH CUSTOMER EXPERIENCE PADA EVENT URBAN VILLAGE TERHADAP BRAND IMAGE UNIVERSITAS TELKOM - M.Si, Arie Prasetio (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Komputer Indonesia, 2021)
Abstract The aims of this research are to determine whether there is a relation and the effect between customer experience to brand image and how much the relation and effect of customer experience on the Urban Village event towards Telkom University brand image. This research is using independent variable named customer experience with dimensions of sense, feel, think, act, and relate. The dependent variable is brand image with dimensions of strength of brand association, favourability of brand association, and uniqueness of brand association. The population in this study is active students of Telkom University who were visitors on the Urban Village event also the amount of the samples taken on this research are 100 respondents using purposive sampling technique. The data analysis techniques of this study consist of normality test, coefficient of determination, Pearson correlation analysis, simple linear regression analysis, and hypothesis testing. Through the hypothesis testing using the t test is shown that value of tcount (10.277) > ttable (1.66), then H0 is rejected, which means that there is the effect of customer experience towards brand image. The coefficient of determination (r) is 51.9%, which means customer experience has an effect of 51.9% towards brand image and the 48.1% effected by other except customer experience. Meanwhile, the correlation coefficient is 0.720 which means customer experience on the Urban Village event has a strong positive relation towards Telkom University brand image